2019
DOI: 10.1371/journal.pone.0214327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug-resistant organisms in nursing homes in Belgium in 2015

Abstract: Objectives Following two studies conducted in 2005 and 2011, a third prevalence survey of multidrug-resistant microorganisms (MDRO) was organised in Belgian nursing homes (NHs) using a similar methodology. The aim was to measure the prevalence of carriage of methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), extended-spectrum β-lactamase producing Enterobacteriaceae (ESBLE) and carbapenemase-producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 47 publications
(62 reference statements)
5
55
2
Order By: Relevance
“…In the primary analysis, we included the 12 studies that adjusted for confounding. [8][9][10]37,39,40,43,45,47,54,55,57 This showed that acid suppression was associated with MDRO colonization (OR = 1.74; 95% CI, 1.40-2.16) ( Figure 2). Among these studies, heterogeneity, as measured using the I 2 method, was 68%.…”
Section: Risk Of Bias and Primary Analysismentioning
confidence: 91%
See 4 more Smart Citations
“…In the primary analysis, we included the 12 studies that adjusted for confounding. [8][9][10]37,39,40,43,45,47,54,55,57 This showed that acid suppression was associated with MDRO colonization (OR = 1.74; 95% CI, 1.40-2.16) ( Figure 2). Among these studies, heterogeneity, as measured using the I 2 method, was 68%.…”
Section: Risk Of Bias and Primary Analysismentioning
confidence: 91%
“…Søgaard et al, 2017 54 Latour et al, 2019 45 Ben-Ami et al, 2006 37 Cheng et al, 2016 39 Falk et al, 2000 40 Hamprecht ters et al 31,34,35 Excluding both studies of UTI did not affect publication bias estimators (eFigure 7 in the Supplement).…”
Section: Publication Biasmentioning
confidence: 99%
See 3 more Smart Citations